Lipodystrophy in insulin users: a literature review - Lopes, Francisco Leilson da Silva; Silva, Ana Carla dos Santos; Linard, Walber Mendes; Pinho, Lucimary Leite de; Paiva, Maria Janaelvia Guimarães; Leite, Ana Caroline Rocha de Melo; Melo, Anielle Torres de; Rodrigues, Lílian Karla Nojosa; Rabelo, Maria Wanessa Freires; Monteiro, David Levy Melo; Silva, Francisco Wanderlei Lima; Filho, José Damião da Silva; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Diabetes is a metabolic syndrome of multiple origins, resulting from lack of insulin and/or the inability of insulin to adequately exercise its insulin. Since 1921, drug therapy by subcutaneous insulin has helped the diabetic patient. Although there are benefits, it is necessary to report that insulin therapy can lead to complications such as lipodystrophy. This is a literature review aimed at evaluating the characteristics of lipodystrophy in insulin users. The first step was to assess the profile of people who develop lipohypertrophy from using insulin. The authors report that most patients who reach a critical level of LH self-administer insulin, a fact that can lead users to settle for the correct administration of therapy. Some reported that the stains had already appeared for years, but patients felt embarrassed to look for someone else to apply. In many who already had prominences in the subcutaneous tissue, the report was that the site was painless. As an expected result, the absence of rotation at the application sites is the main cause for the appearance of LH. From the moment the patients were diagnosed by the professionals and started to be instructed about the rotation of the application sites, the LH rate dropped to 8% of the people. Therefore, insulin users need